IMPLEMENTASI KEBIJAKAN GERAKAN LITERASI SEKOLAH (GLS) DI MI/SD - Zumratun, Zumratun (Prodi PGMI STIT Sunan Giri Bima, 2022)
The school literacy movement is an educational policy that strives for students' literacy skills in mathematics, science, reading and writing. The school literacy movement is also considered as a movement that aims to make schools a place for learning (reading and writing) so that citizens can always be literate throughout life by involving the public. This school literacy movement must be encouraged because the Indonesian people's interest in reading and writing is still relatively minimal. This school literacy program is expected to be able to arouse interest in reading and writing from an early age. So, with this writing, the author invites schools and all levels of society, more specifically to student parents, to be able to support government policies regarding the school literacy movement. In writing this article, the author uses the method of writing literature studies with literature and the internet. GLS implementation at the MI/SD level is discussed according to the policies the government wants. Matters related to education policy and the school literacy movement are discussed systematically.